Efeito da espessura, cor e translucidez de uma cerâmica de dissilicato de lítio sobre a transmissão da luz halógena e de diodo emissor de luz , o grau de conversão e a microdureza de diferentes cimentos resinosos - Carolina Nemesio de Barros Pereira (2015)
This study evaluated the effect of thickness, shade and translucency of a ceramic on light emitting diode (LED) and halogen light (HAL) transmission, and the degree of conversion and microhardness of different resin cements. The factors studied were thickness (1, 2, 3, 4, 5mm), shade (A1, A2, A3, A3.5) and translucency (high-HT or low-LT) of a lithium disilicate glass-ceramic and light sources (halogen and LED). Fourty ceramic blocks (IPS e.max CAD, Ivoclar Vivadent) were cut and crystallized (200 samples). The emission spectra of HAL (Demetron LC) and LED (Bluephase) were determined. Light intensity (mW/cm2) incident on the detector and the light transmitted through each ceramic sample were measured in triplicate for each light unit. A linear regression model was used for statistical analysis. The light absorption coefficient () of ceramics for the different shades and translucency were obtained using the Lambert-Beer formula from logn of measured thickness. The degree of conversion (DC) by FT-Raman spectroscopy and Knoop microhardness (KHN) of resin cements RelyX ARC, RelyX U200 and RelyX Veneer were measured without barrier or by interposing ceramics (2, 3 or 4mm-thick), shade (A2, or A3 A3.5) and translucency (HT or LT), n=3. GC and KHN of the same cements without photoactivation were evaluated as a chemical pattern compared to C&B cement (n=3). Data analysis (=5%) were performed by linear regression for light transmission ANOVA and Tuckey for conversion degree; Kruskal-Wallis, Dunntest and Bonferroni correction for microhardness. Light intensity was 1350mW/cm2 for LED and 950mW/cm2 for HAL. There was a significant interaction between light source and translucency (p=0.008) and a strong negative correlation (r=-0.845; p<0.001) between ceramic thickness and light transmission percentage (TP). Increasing a unit in thickness led to a mean reduction of 3,17 in TP. There was no significant difference in TP (p=0.124) between the shades A1 (ß1=0) and A2 (ß1=-0.45) but a significant reduction occurred for A3 (ß1=-0.83) and A3.5 (ß1=-2.18). The HAL/HT interaction showed higher PT (ß1=0) than LED/HT (ß1=-2.92) and HAL/LT (ß1=-3.75). LED/LT showed the lower PT (ß1=-5.58). From the regression model, an equation was obtained to determine PT estimated using ß1 values of each variable. There was effect of ceramic shade, translucency and thickness on the conversion degree of resin cements RelyX ARC, U200 e Veneer (p<0.0017), but there was no effect of light source (p=0.9512). Higher values of conversion degree were observed for C&B self-cured and RelyX Veneer light-cured cement, followed by ARC and U200 dual cements. U200 and ARC without photoactivation showed the lowest degree of conversion. For KHN, there was no significance for the factors shade (p=0.1717) and light source (p=0.1421). Ceramic translucency and thickness, and type of resin cement presented effect on the KHN (p=0.0001). The KHN values were higher for U200, followed by ARC. The lowest values were found for Veneer. High translucency ceramics were associated with higher KHN values of the underlying cement compared to the low translucency samples. In conclusion, there were differences in ceramics behavior, which absorb less light than when exposed to HAL compared to the LED. The interaction LED/LT and the increased ceramic thickness produced lowest PT values. Shades A1 and A2 allowed higher PT than A3 and A3.5. The proposed equation allowed estimating TP through a restoration from shade, translucency and light source. Degree of conversion has the effect of ceramic shade, translucency and thickness. KHN was dependent of ceramic translucency, followed by thickness. HAL produced less energy density, but there was no difference between light sources concerning KHN or conversion degree.